2019
DOI: 10.24843/ejmunud.2019.v08.i08.p13
|View full text |Cite
|
Sign up to set email alerts
|

Peran Kepuasan Kerja Memediasi Pengaruh Stres Kerja Terhadap Kinerja Karyawan Housekeeping Department Fave Hotel

Abstract: Companies must be able to maintain employee performance to remain stable and even increase. Satisfied employees are effective and well-performing workers. The purpose of this study was to determine the direct effect of work stress and job satisfaction on employee performance, to determine work stress on employee job satisfaction, and to determine the effect of Job Satisfaction in mediating the effect of work stress on employee performance. The population in this study were 47 Fave Hotel Housekeeping Department… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1
15

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 0 publications
2
5
1
15
Order By: Relevance
“…This means that employees with low stress levels will have higher performance compared to employees with higher stress levels. However, the results of this study contradict the results of this study (Prawira & Suwandana, 2019;Sandiartha & Suwandana, 2020;revealed that there is a significant negative relationship between work stress variables and employee performance.…”
Section: Discussion the Effect Of Work Stress On Employee Performancecontrasting
confidence: 99%
“…This means that employees with low stress levels will have higher performance compared to employees with higher stress levels. However, the results of this study contradict the results of this study (Prawira & Suwandana, 2019;Sandiartha & Suwandana, 2020;revealed that there is a significant negative relationship between work stress variables and employee performance.…”
Section: Discussion the Effect Of Work Stress On Employee Performancecontrasting
confidence: 99%
“…Hal ini dikarenakan tingginya beban kerja pegawai tanpa di imbangi dengan gaji yang sesuai akan menurunkan tingkat kepuasan pegawai. Penelitian lain oleh (Prawira & Suwandana, 2019) yang dilakukan di Fave Hotel Kartika Plaza, yang menggambarkan hasil bahwa stres kerja berpengaruh negatif dan signifikan terhadap kepuasan kerja. Hal ini dikarenakan adanya masalah pekerjaan yang melebihi jam kerja tanpa diberikan insentif tambahan.…”
Section: Pendahuluanunclassified
“…Berdasarkan hasil penelitian terdahulu ditemukan bahwa kepuasan kerja juga mempengaruhi kinerja pegawai, seperti pada penelitian Prawira & Suwandana (2019) pada Fave Hotel Kartika Plaza yang menyatakan bahwa terdapat pengaruh positif dan signifikan antara variabel kepuasan kerja dan kinerja pegawai. Hal ini dikarenakan timbulnya hubungan yang erat antara atasan dan bawahan mampu meningkatkan kinerja pegawai.…”
Section: Pendahuluanunclassified
See 2 more Smart Citations